PENERAPAN METODE PEMBELAJARAN ROLE PLAYING UNTUK MENINGKATKAN KONSENTRASI SISWA PADA MATA PELAJARAN PKN KELAS XI DI SMAN 1 BLEGA - Holipah; Ernawati; Bagus Imam Faisal; Diah Retna Yuniarti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine whether the implementation of the role playing method can increase students' concentration in civics learning at SMAN 1 Blega. The study employs a descriptive qualitative approach with 32 students from class XI as research subjects. Data collection techniques include observation through teaching module implementation sheets and student learning concentration questionnaires. The results indicate that the implementation of the PKn teaching module using the role-playing method is in the